Controle de plantas daninhas com bioherbicida produzido por fermentação de Diaporthe schini - Brun, Thiarles (2020)
Weed control is essential to ensure the productivity and quality of food production. Chemical control is the most used, but the demand for healthier food, concern for the environment and the health of farmers, has increased the search for other control methods. This work aims to improve the herbicidal effect of bioherbicides produced by solid state fermentation and to compare this technique with submerged fermentation using the fungus Diaporthe schini, in addition to studying the use of spray drying for microencapsulation. First, solid state fermentation was carried out to determine the best conditions for cultivation of the fungus with herbicidal action in an absorption test on detached leaf of Cucumis sativus. The best result found with herbicidal action in solid state fermentation was compared with submerged fermentation, carried out through physical-chemical characterization and bioherbicidal effect. In addition, different adjuvants for spray drying microencapsulation were studied and the equipment parameters were optimized. All conditions were evaluated according to the postemergence bioherbicidal effect of Bidens pilosa, Amaranthus viridis, Echinocloa crusgalli and Lollium multiflorum. The best cultivation condition found for solid state fermentation was 40% moisture and without corn maceration water (AMM) and soybean meal (FS) supplementation, presenting necrosis in C. sativus leaves. D. schini broth obtained by submerged fermentation was more effective than solid state fermentation for weed control, showing weed growth inhibition and better physicochemical characteristics. Microencapsulation with lactose adjuvant and in the condition of the central point of spray drying planning with an inlet temperature of 100ºC, flow of drying air 1.5 m3/min and feed flow of 0.22 L/min showed the greatest effect bioherbicide on weeds. Submerged fermentation combined with microencapsulation by spray drying is an important tool for the production of D. schini bioherbicide, and may provide subsidies for further research.